Faktor-Faktor yang Berhubungan dengan Proses Klaim BPJS Kesehatan pada Pasien Sectio Caesaria di Rumah Sakit Umum Daerah Pakuhaji - Amelia Oktapiyani; Elza Fransisca; Amika Rois (Lembaga Pengembangan Kinerja Dosen, 2024)
The social assurance program in Indonesia is formed by legal organization called Badan Penyelenggara Jaminan Sosial (BPJS) which is expected to provide appropriate health facilities for the middle low community. One of the diagnoses and surgery claimed by BPJS Kesehatan is sectio caesar where the caesar section has been increased significantly year by year, but there so many factors that effect the claim process before submitted to the BPJS. The purpose of this research is to find out what the factors that related to the submitting medical record for BPJS claims and how many files are returned from the casemix section to the BPJS claim process for sectio caesar patients at Pakuhaji Public Hospital. The sample of this study is 97 medical records of sectio Caesar patient that will be proceed for the BPJS claim. This study used a quantitative cross-sectional approach. This study found that incomplete medical record doucment and incorrect codes. And the result of this study is the completeness of the file and the accuracy of the code had a significant relation with the claim process, meanwhile the file collection at Pakuhaji Public Hospital hasn’t relation with the claim process because the results were constant. From the result, will be better if Pakuhaji Public Hospital provides the socialization, training for medical records officer and cross-checking medical records file completeness and code accuracy before being submitted to casemix so that in the future it will facilitate the claim process.